VD_FINDINFO Pron / 2014 / 11 vom 28. Januar 2014 - VD Tribunal cantonal (2014)
PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE, MÉDECIN, PROCÈS DEVENU SANS OBJET | 426 CC, 439 al. 1 CC, 439 al. 1 ch. 1 CC, 439 CC, 450 CC, 450e CC, 242 CPC (CH)